Cation‐Controlled Assembly of Polyoxotungstate‐Based Coordination Networks. Issue 38 (21st July 2020) - Chen, Linfeng; Turo, Michael J.; Gembicky, Milan; Reinicke, Ruth A.; Schimpf, Alina M.
Abstract: The Preyssler polyoxoanion, [NaP5 W30 O110 ] 14− (P5 W30 ), is used as a platform for evaluating the role of nonbridging cations in the formation of transition‐metal‐bridged polyoxometalate (POM) coordination frameworks. Specifically, the assembly architecture of Co 2+ ‐bridged frameworks is shown to be dependent on the identity and amount of alkali or alkaline‐earth cations present during crystallization. The inclusion of Li +, Na +, K +, Mg 2+, or Ca 2+ in the framework synthesis is used to selectively synthesize five different Co 2+ ‐bridged P5 W30 structures. The influence of the competition between K + and Co 2+ for binding to P5 W30 in dictating framework assembly is evaluated. The role of ion pairing on framework assembly structure and available void volume is discussed. Overall, these results provide insight into factors governing the ability to achieve controlled assembly of POM‐based coordination networks. Abstract : Networking : The Preyssler polyoxoanion, [NaP5 W30 O110 ] 14− (P5 W30 ), was used to evaluate the role of nonbridging cations in the formation of transition‐metal‐bridged polyoxometalate (POM) coordination frameworks. The assembly architecture of Co 2+ ‐bridged frameworks is dependent on the identity and amount of alkali or alkaline‐earth cations present during crystallization. Overall, these results provide insight into factors governing controlled assembly of POM‐based coordination networks.